Case Report: A patient with a novel heterozygous IRF8 variant with repeated infection and immune-mediated organ disease, but without disseminated mycobacterial disease despite BCG immunization - Chiang, Samuel C. C.; Owsley, Erika; Husami, Ammar; Akeno, Nagako; Cobb, Cristina M.; Yang, Li; Marsh, Rebecca A.; Myers, Kenneth A.; Rubin, Tamar S. (Frontiers in Immunology, 2025)
We describe a patient with a novel, de novo heterozygous IRF8 variant (c.1182dup) who presented with viral and bacterial susceptibility, lymphoproliferation, and liver and lung diseases characteristically seen in patients with underlying inborn errors of immunity, but without disseminated mycobacterial disease, despite vaccination with Bacillus Calmette-Guérin (BCG), the live attenuated vaccine form of Mycobacterium bovis. Laboratory evaluation revealed an absence of circulating plasmacytoid dendritic cells (pDC) with poor IL-12p70 and IFN-γ secretion upon LPS stimulation, and poor IFN-γ secretion upon PHA stimulation. In contrast, another patient with a different novel, de novo heterozygous IRF8 variant (c.10C>T) had milder early life infection susceptibility, but no lymphoproliferation, nor immune-mediated organ disease, and no prior exposure to BCG vaccine. They had a normal number of circulating pDC, and IL-12p70 production upon LPS stimulation that was no different compared to the mother who did not possess the IRF8 variant, and with normal IFN-γ secretion upon PHA stimulation. Our findings support impaired IRF8 function in the first patient, but less for the second patient. We propose that altered DC subsets and deficient cytokine production can assist with IRF8 VUS (variant of unknown significance) interrogation. This report expands current knowledge of mono-allelic human IRF8 variants.